2016
DOI: 10.1016/j.bdq.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of digital PCR to the investigation of pediatric-onset genetic disorders

Abstract: Early-onset rare diseases have a strong impact on child healthcare even though the incidence of each of these diseases is relatively low. In order to better manage the care of these children, it is imperative to quickly diagnose the molecular bases for these disorders as well as to develop technologies with prognostic potential. Digital PCR (dPCR) is well suited for this role by providing an absolute quantification of the target DNA within a sample. This review illustrates how dPCR can be used to identify gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Meanwhile, MIMT1 is an MER1 repeat-containing imprinted transcript, which can undergo hypermethylation in the placenta of intrauterine growth-restricted fetuses in cattle [ 51 ], and truncation of exons 3 and 4 of the MIMT1 gene caused intrauterine growth restriction [ 52 ]. Furthermore, the transmembrane p24 trafficking protein family member, DDX28, was used to investigate pediatric-onset genetic disorders by digital PCR [ 53 ]. However, the biological roles of the two genes (TMED and LOC151174) in cancer are yet unknown, and this has to be researched further in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, MIMT1 is an MER1 repeat-containing imprinted transcript, which can undergo hypermethylation in the placenta of intrauterine growth-restricted fetuses in cattle [ 51 ], and truncation of exons 3 and 4 of the MIMT1 gene caused intrauterine growth restriction [ 52 ]. Furthermore, the transmembrane p24 trafficking protein family member, DDX28, was used to investigate pediatric-onset genetic disorders by digital PCR [ 53 ]. However, the biological roles of the two genes (TMED and LOC151174) in cancer are yet unknown, and this has to be researched further in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this inverse relationship, SMN2 copy number is being used as a criterion for inclusion in SMA clinical trials. dPCR can accurately measure copy number variations found in many pediatric-onset disorders including SMA [41]. We and others have demonstrated that dPCR provides an accurate and reliable measurement of SMN2 copy number [21;42].…”
Section: Discussionmentioning
confidence: 99%
“…The Absolute Q dPCR quadruplex assay approach could be extended to identification of copy number variations associated with other diseases, in addition to SMA. dPCR has been used to identify rare gene variants as well as differences in copy number of multiple genes associated with pediatric-onset disorders (reviewed in 24 ). We have demonstrated that this system can identify a rare single nucleotide variant ( EGFR(T790M) ) associated with non-small cell lung carcinoma as well as fusion genes ( BCR-ABL1 and CCDC88C-FLT3 ) that are associated with different types of cancer 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Digital PCR (dPCR) alleviates the limitations previously noted to provide absolute quantification of a target gene within a sample for molecular diagnostics and prognostics 24 . With dPCR, the prepared PCR sample is distributed across a large number of physically isolated micro-reaction partitions so that each partition will have single digit counts of template DNA or none at all 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%